STRATEGI KOMUNIKASI PEMERINTAHAN NAGARI SARIAK KECAMATAN SUNGAI PUA KABUPATEN AGAM DALAM MELAKUKAN PROGRAM VAKSINASI COVID-19 - Filzah Puti Andevi; Penmardianto Penmardianto (Universitas Pahlawan Tuanku Tambusai, 2022)
Communication is a message conveyed by the communicator to the communicant either directly or indirectly. In the current era of Covid-19, the central government is carrying out several policies to prevent the spread of Covid-19, one of which is vaccines. However, the amount of rejection and antipathy given by the public to the policies carried out by the government has made the development of Covid-19 still high. Of course this is very unfortunate, so the right strategy is needed to invite the public to do the vaccine. This is what the Nagari Sariak Government is doing in carrying out a communication strategy to carry out the co-19 vaccination program. This research was conducted using a descriptive qualitative approach which aims to reveal in-depth phenomena about the da'wah strategy carried out by the Nagari Sariak Government, Sungai Pua District, Agam Regency in carrying out the co-19 vaccination program. This research is examined by using several theories about communication strategy. The results of this study indicate that the communication strategy used by the Nagari Sariak Government includes a five-step strategy, cut and center, philip lesly, and marketing promotion implemented in the form of research, policy formulation, planning, communication activities, measurement and reporting. While the supporting factors driving the Covid-19 vaccination program include good cooperation between the Nagari Sariak Government and the National Team Babhinkabtimnas, Babinsa and health workers, strategic and easy-to-access places for vaccines for the community, complete availability of vaccines. Keywords: Communication Strategy, Nagari Sariak Government, Covid-19 Vaccination